2007
DOI: 10.1007/s10433-007-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

What really matters in the social network–mortality association? A multivariate examination among older Jewish-Israelis

Abstract: The aim of the inquiry was to examine the social network-mortality association within a wider multivariate context that accounts for the eVects of background framing forces and psychobiological pathways. The inquiry was based upon the Berkman et al. (2000) conceptual model of the determinants of health. Its main purpose was to identify the salient network correlates of 7-year all cause mortality among Jewish men and women, aged 70 and over, in Israel (n = 1,811). The investigation utilized baseline data from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 56 publications
4
26
0
1
Order By: Relevance
“…If people choose activities in order to maximize their wellbeing, one would expect the least happy people to attend the most often, since they would benefit most from these boosts, leading to a negative correlation rather than the positive one we found. In addition, Litwin (2007) found that after controlling for covariates such as social involvement and physical health, religious involvement only improved mortality risk for those who attended services regularly, consistent with our theory that lasting change only occurs with frequent involvement.…”
Section: Discussionsupporting
confidence: 85%
“…If people choose activities in order to maximize their wellbeing, one would expect the least happy people to attend the most often, since they would benefit most from these boosts, leading to a negative correlation rather than the positive one we found. In addition, Litwin (2007) found that after controlling for covariates such as social involvement and physical health, religious involvement only improved mortality risk for those who attended services regularly, consistent with our theory that lasting change only occurs with frequent involvement.…”
Section: Discussionsupporting
confidence: 85%
“…This is because the importance of spousal support in different countries or cultures varies (Litwin 2007), and because there is a significant difference in the composition of personal support networks between Chinese and Westerners, with the former preferring turning to non-kin such as friends and coworkers when they are confronting emotional issues . In China, the social support received from friends, relatives, coworkers, and neighbors is more powerful than spousal support at oldest-old ages in determining healthy longevity .…”
Section: Discussionmentioning
confidence: 96%
“…At the individual level, many studies have shown that religion is linked to various measures of physical health, such as lower rates of coronary disease, emphysema and cirrhosis (Comstock and Partridge 1972), lower blood pressure (Larson et al 1989), and longer life expectancy (George et al 2002;Hummer et al 1999;Idler and Kasl 1997;Koenig 1997;Larson et al 1997;Litwin 2007;Plante and Sherman 2001;Seybold and Hill 2001) Researchers investigating a wide array of psychological disorders-such as depression-have generally found religious involvement to be related to better mental health as well (Hackney and Sanders 2003;Kendler et al 2003;Larson et al 1992;Smith et al 2003).…”
Section: The Benefits Of Religionmentioning
confidence: 99%